Students Motivation and Grit in Learning English at Lembaga Pendidikan dan Pengembangan Profesi (LP3I) of Bengkulu - Nurzalinda Arin (Linguistic, English Education and Art (LEEA) Journal, 2022)
Motivation is an attitude that influences a person to achieve specific goals. Grit is persistence to achieve goals over the long term. This study is aimed to determine the motivation and persistence of students in learning English. This study used a quantitative descriptive design. The subjects of this study were 102 students at LP3I College Bengkulu. The data collection technique in this study was a questionnaire survey using Google Form. The data were calculated in percentage. The findings of this study indicate that student motivation at LP3I College Bengkulu was very high. Extrinsic motivation was higher than intrinsic motivation. In addition, extrinsic motivation was the main reason why most students learn English based on the results of the questionnaire. The result of the study also shows that students' persistence was very high. The results of students' perceptions of motivation and persistence showed that students had positive perceptions. This proves that students with high motivation and Grit have good results in achieving learning goals. Based on this research, it is recommended for the syllabus designers to streamline teaching materials to be more specific according to the majors studied and for English language teachers to improve teaching methods so that motivation and perseverance in learning can be applied properly. Keywords: Grit, Learning English, Motivation